1997
DOI: 10.1007/s11666-997-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Graded plasma spraying of premixed metalceramic powders on metallic substrates

Abstract: The mismatch between the thermal expansion coefficients of ceramics and metals and the differential stresses it causes at the interface create problems in metal to ceramic joining. Research has been conducted to solve this problem in thermal barrier coating technology. Previous studies have considered metal-ceramic multilayers or graded-coatings, which include a metallic bond coat. In this study, a graded plasma-sprayed metal-ceramic coating is developed using the deposition of premixed metal and ceramic powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…It is believed that adhesion is substantially dependent on the microstructure aspects generated under process conditions. 43 Higher bond strength can be seen for a coating sprayed under optimum spray condition due to its minimum porosity ( Fig. 4e and f).…”
Section: Chemical Adhesionmentioning
confidence: 91%
“…It is believed that adhesion is substantially dependent on the microstructure aspects generated under process conditions. 43 Higher bond strength can be seen for a coating sprayed under optimum spray condition due to its minimum porosity ( Fig. 4e and f).…”
Section: Chemical Adhesionmentioning
confidence: 91%
“…Ceramic coatings on relatively ductile metal-alloy substrates behave in a complex way under static mechanical loads and/or thermal cycling conditions and hence result in poor interfacial mechanical properties. Recent studies have shown improvement of coating properties with premixed metalceramic powders [14][15][16]. In the view of this, the present study explores the coating potential of Cu Slag-Al composite for different engineering and structural applications.…”
Section: Journal Of Coatingsmentioning
confidence: 98%
“…As trincas são devidas às tensões residuais provocadas pela oxidação da camada de ligação metálica em altas temperaturas (formação e crescimento da TGO), devido à permeabilidade da camada cerâmica porosa, e às diferenças de expansão térmica cíclica (fadiga térmica no aquecimento e resfriamento dos componentes, durante o serviço), resultantes da diferença de cerca de 30 % no coeficiente de expansão térmica entre a zircônia parcialmente estabilizada e a camada de ligação metálica [2,3,4]. Diversas pesquisas têm sido realizadas na busca de solucionar estes problemas, envolvendo, inclusive, o conceito de revestimentos graduados [19,20], pré ou pós-tratamentos dos revestimentos [21,22,23] e adição de dopantes [24,25].…”
Section: Desenvolvimentos Desafios E Perspectivasunclassified
“…Lima e Trevisan [20] estudaram um revestimento para barreira térmica com graduação dos pós metálico e cerâmico, sem utilização de bond-coat metálico convencional, eliminando a interface abrupta metal-cerâmica entre a camada de ligação metálica e a camada externa cerâmica, típica dos sistemas duplex. Como resultado, o sistema com graduação de mistura 25% metal -75% cerâmica na interface com o substrato metálico apresentou resultados bem próximos ao sistema convencional duplex, quando avaliado pela resistência adesiva, dureza, microestrutura e estabilidade de fases, em espessuras de até 300 µm.…”
Section: Influência Das Tensões Residuaisunclassified